HUBUNGAN SELF-ESTEEM DENGAN KEBERANIAN MELAPOR CYBERBULLYING DI SMP - Maulidia Farah Diba; Muhammad Andri Setiawan; Ririanti Rachmayanie Jamain (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
The development of digital technology has created opportunities for cyberbullying to occur among adolescents, particularly junior high school students. However, the reporting rate remains low, and one variable assumed to be related to the courage to report is self-esteem. Previous studies have mostly positioned self-esteem as a factor related to whether an individual becomes a victim or perpetrator of cyberbullying, whereas this study differs by focusing on the courage to report. This study aims to analyze the relationship between self-esteem and the courage to report cyberbullying in junior high school. A quantitative correlational approach was used with a sample of 167 seventh-grade students at SMP Negeri 24 Banjarmasin, selected using purposive sampling. Data were collected using two questionnaires, namely a self-esteem questionnaire and a courage to report cyberbullying questionnaire, and were then analyzed using Pearson’s Product Moment correlation. The results showed that students’ self-esteem and courage to report cyberbullying were both in the moderate category. In addition, self-esteem had a positive, significant, and strong relationship with the courage to report cyberbullying. In other words, the higher the students’ self-esteem, the greater their courage to report. These findings indicate that students’ self-esteem needs to be strengthened through guidance and counseling services because it is related to students’ courage to report cyberbullying cases. ABSTRAK Perkembangan teknologi digital telah membuka celah munculnya cyberbullying di kalangan remaja, khususnya pada siswa SMP. Namun, tingkat pelaporan masih rendah, dan salah satu variabel yang diduga berkaitan dengan keberanian melapor adalah self-esteem. Kajian terdahulu banyak menempatkan self-esteem sebagai faktor yang berkaitan dengan posisi seseorang sebagai korban atau pelaku cyberbullying, sedangkan penelitian ini berbeda karena berfokus pada keberanian melapor. Penelitian ini bertujuan untuk menganalisis hubungan antara self-esteem dengan keberanian melapor cyberbullying di SMP. Pendekatan kuantitatif korelasional digunakan dengan sampel sebanyak 167 siswa kelas VII SMP Negeri 24 Banjarmasin yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan menggunakan dua angket, yaitu angket self-esteem dan angket keberanian melapor cyberbullying, kemudian dianalisis dengan Pearson Product Moment. Hasil penelitian menunjukkan bahwa self-esteem dan keberanian melapor cyberbullying siswa sama-sama berada pada kategori sedang. Selain itu, self-esteem memiliki hubungan positif, signifikan, dan kuat dengan keberanian melapor cyberbullying. Dengan kata lain, semakin tinggi self-esteem siswa, semakin tinggi pula keberanian mereka untuk melapor. Temuan ini menunjukkan bahwa self-esteem siswa penting diperkuat melalui layanan bimbingan dan konseling karena berkaitan dengan keberanian siswa dalam melaporkan kasus cyberbullying.